PENINGKATAN MOTIVASI BELAJAR PESERTA DIDIK MELALUI PENERAPAN MODEL PEMBELAJARAN CORE DI KELAS X SMA NEGERI 15 SEMARANG - Muhammad Naufal Majid; Eny Winaryati (LitbangMu Jawa Tengah and Teacher Professional Education UNIMUS, 2024)
This study aims to identify and improve students' learning motivation through the implementation of the CORE learning model based on an active and collaborative learning approach. This study was conducted in two cycles, with the subjects of the study being grade X students in a high school. In the first cycle, students' learning motivation was indicated to be low, with an average score of 2.8 on a Likert scale of 1-5, which was reflected in minimal participation, low initiative to ask questions, and less than optimal quality of assignments. In response to these findings, the second cycle involved the implementation of various learning strategies, such as providing simple rewards, using interesting learning media, a personal approach, and dividing groups based on student abilities. The results of the second cycle showed a significant increase, with the average score of student motivation increasing to 3.9, as well as positive changes in class participation, quality of interaction between students, and better assignment results. This increase in motivation not only impacts student engagement in learning, but also improves their understanding of the material being taught. This study concludes that learning strategies that actively involve students can be effective in improving learning motivation, as well as providing a basis for further development in the implementation of more innovative and inclusive learning.